Nucleophilic Ring‐Opening of 1, 6‐Anhydrosugars: Recent Advances and Applications in Organic Synthesis. Issue 24 (23rd June 2021) - Hazelard, Damien; Compain, Philippe
Abstract: 1, 6‐Anhydrosugars provide a valuable source of building blocks for the synthesis of a wide range of compounds of interest, from natural products to medicines. The unique reactivity of these functionalized, homochiral synthons is controlled by the 1, 6‐anhydro bridge which locks the conformation of the pyranose ring, provides a dual protection of two hydroxyl groups, and either protects or activates the anomeric position. The concomitant release of the primary hydroxyl group at C‐6 during the ring‐opening step limits protecting group manipulations and enables the design of highly convergent synthetic strategies. In recent years, many examples of stereocontrolled ring‐opening of 1, 6‐anhydrosugars by a diversity of nucleophiles, including hetero‐ and C ‐nucleophiles, have been reported. The purpose of this review is to present an overview of the recent advances, applications and challenges associated with this process. Abstract : The stereocontrolled ring‐opening of 1, 6‐anhydrosugars with various nucleophiles leading to natural products, glycomimetics and other compounds of biological interest is covered with recent, relevant examples.